Christian Responses to Modern Slavery - Reaves, Jayme (Trinity College Dublin, 2007)
This research project explores the theological and ethical issues around modern slavery and movements to abolish it. Topics include: human trafficking; human rights; racism; theological language and doctrines; Christian ethics, values and social practice.
Exhibited at the second Glucksman Memorial Symposium on June 13th 2007
Keywords: Modern slavery; Slavery -- Christian response